GAYA KEPEMIMPINAN SEBAGAI PEMODERASI PENGARUH PARTISIPASI ANGGARAN DAN ASIMETRI INFORMASI PADA SENJANGAN ANGGARAN - Taufik, Ahmad; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 20 No 2 (2017)DO - 10.24843/EJA.2017.v20.i02.p14, 2017)
This study aims to determine the leadership style as the moderating influence of budget participation and asymmetry of information on budgetary slack (Empirical Studies in Central Lombok Regency SKPD). This study was conducted on 39 SKPD located in Central Lombok regency. The population of this research is SKPD officials in Central Lombok. The sampling method used in this research is purposive sampling. The number of samples in this study was 117 respondents. Data was collected by using a survey method using questionnaires and interviews. The data analysis technique used is multiple linear regression and Moderated Regression Analysis (MRA). Based on the results of analysis show that budget participation a positive effect on budgetary slack. Asymmetry of information has a positive effect on budgetary slack. Strengthen leadership styles influence of budget participation on budgetary slack. The leadership style strengthen the influence of information asymmetry on budgetary slack.
Keywords: Budget Participation, Information Asymmetry, Leadership Style, Budgetary Slack